Training, Recruitment, Placement and Retention of Health Professionals - SOLID Nepal; Merlin Nepal (SOLID Nepal 2011, 2012)
There is increasing global consensus on the need to consider the health system in its entirety, taking into consideration the limitations of public health budgets and the use of the private sector as an ‘ally in the struggle to provide higher quality services to a greater number of people’ (4). The role of Public Private Partnership (PPP) can therefore be used as a way to optimise the use of available resources and address the challenges facing the public health sector. In Nepal, where there is a considerably higher number of health staff produced by the private sector, yet the quality and capacity of those institutions and health workers is questionable, the nature of PPP in the country raises some serious concerns. On the other hand, it also provides opportunities for both sectors to address their weaknesses and improve capacity through strengthened partnership. This report examines the challenges faced by the public sector in training, recruitment, placement and retention of health workers, and explores ways in which the public and private sectors can work together to improve health outcomes in the country.